Lao Biodiversity : A Priority for Resilient Green Growth - World Bank (World Bank, Washington, DC, 2020)
The Lao People’s Democratic Republic is in one of the ten most important global biodiversity ecoregions and home to some of the world’s biologically richest and most endangered species. The biodiversity endowment is crucial to the Lao economy. The goods and ecosystem services it provides are essential to reduce poverty, secure livelihoods, and drive a greener economic growth model. But Lao PDR’s biodiversity is in danger. The highest priority threats to the country’s biodiversity values include climate change, illegal logging and wildlife trade, infrastructure development in and around protected areas, and expansion of agriculture and settlements. This policy note is a summary of the report which aims to highlight key issues to add value to the the upcoming Lao landscapes and livelihoods project with financing from the World Bank and the global environment facility.